ILMU FALAK (Dimensi Kajian Filsafat Ilmu) - Mujab, Sayful; Nasir, M. Rifa Jamaludin (Universitas Islam Negeri Mataram, 2020)
Artikel ini membahas bagaimana Ilmu Falak diulas dalam filsafat ilmu. Data penelitian digali dari berbagai literatur ilmiah dan selanjutnya dianalisis secara kualitatif. Hasil penelitian menunjukkan bahwa Ontologi, Epistemologi, dan Aksiologi Ilmu Falak menjadi kajian penting bagi eksistensi Ilmu Falak sebagai ilmu yang mapan dalam dunia ilmu. This article discusses how Ilmu Falak is reviewed in the philosophy of science. The research data were extracted from various scientific literature and then analyzed qualitatively. The results showed that the Ontology, Epistemology, and Axiology of Ilmu Falak became an important study for the existence of Ilmu Falak as a science that is well established in the world of science.